A multi-institution study: comparison of the heating patterns of five different MR-guided deep hyperthermia systems using an anthropomorphic phantom. (1st January 2020) - Curto, Sergio; Mulder, Hendrik Thijmen; Aklan, Bassim; Mils, Oliver; Schmidt, Manfred; Lamprecht, Ulf; Peller, Michael; Wessalowski, Ruediger; Lindner, Lars H.; Fietkau, Rainer; Zips, Daniel; van Holthe, Netteke; et al.
Abstract: Introduction: Within the hyperthermia community, consensus exists that clinical outcome of the treatment radiotherapy and/or chemotherapy plus hyperthermia (i.e. elevating tumor temperature to 40 − 44 °C) is related to the applied thermal dose; hence, treatment quality is crucial for the success of prospective multi-institution clinical trials. Currently, applicator quality assurance (QA) measurements are implemented independently at each institution using basic cylindrical phantoms. A multi-institution comparison of heating quality using magnetic resonance thermometry (MRT) and anatomical representative anthropomorphic phantoms provides a unique opportunity to obtain novel QA insights to facilitate multi-institution trial evaluation. Objective: Perform a systematic QA procedure to compare the performance of MR-compatible hyperthermia systems in five institutions. Methods and materials: Anthropomorphic phantoms, including pelvic and spinal bones, were produced. Clinically relevant power of 600 watts was applied for ∼12 min to allow for 8 sequential MR-scans. The 3D-heating distribution, steering capabilities, and presence of off-target heating were analyzed. Results: The evaluated devices show comparable heating profiles for centric and eccentric targets. The differences observed in the 3D-heating profiles are the result of variations in the exact phantom positioning and applicator characteristics, whereby positioning of the phantom followed current ESHO-QA guidelines. Conclusion: Anthropomorphic phantoms were used to perform QA-measurements of MR-guided hyperthermia systems operating in MR-scanners of different brands. Comparable heating profiles are shown for the five evaluated institutions. Subcentimeter differences in position substantially affected the results when evaluating the heating patterns. Integration of advanced phantoms and precise positioning in QA-guidelines should be evaluated to guarantee the best quality patient care.